Communication + Surveillance - J. Macgregor Wise (communication +1, 2022)
This essay argues for expanding the engagement of communication studies with surveillance studies by seeing surveillance itself as a communicative practice.Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023